Wind Rose Analysis for UTHM and Possible Pollution Sources Zone - AZIZI, MOHAMAD; Hashim, Nor Haslina (Progress in Engineering Application and Technology, 2021)
The nearby urban area such as industrial park or a city can contribute of factor of increased distance from the pollution concentration. The concentrations of pollutants that dispersed in atmosphere then can be affected by several factors such as wind speed, wind direction, air concentration, temperature and precipitation. Pollution that caused by non-point sources and unknown sources can make the source identification become more difficult. Therefore, in this study the wind speed and the wind direction at three different sites at UTHM - Parit Raja Campus were analyzed in order to predict the possible pollution sources zones. Due to the Movement Control Order (MCO) during COVID-19 pandemic, the analysis was only conducted to the previous collected PM2.5 data from 4 March 2020 until 31 July 2020 in three different location at UTHM Parit Raja campus. The data obtained then was analyzed for the daily concentration and was reported per month. Then, WRPlot View software then was used to generate the wind rose and the pollution rose for the selected months. The results showed that the maximum concentration of PM2.5 is 113.71 µg/m3 in 30 July 2020 at Post Guard. The wind rose analysis showed that most of the time wind was directed from southern east for March 2020, southern east for April 2020, northern east for June 2020 and northern west. The maximum wind speed for 4 months was 0.855m/s. Most of the time, wind speed was measured at 1.05 m/s on June 2020, Finally, by analyzing the wind rose and the pollution rose of each location, a projection of pollution sources was made to predict the possible pollution sources that contributed to the PM2.5 concentration to UTHM - Parit Raja Campus during the studied months.